KEBIJAKAN DISTRIBUSI DALAM PEMBANGUNAN EKONOMI ISLAM - Irfan Saefuloh (Jurnal Pelita Nusa, 2021)
Income distribution is the most important aspect because it relates to how individuals can allocate resources efficiently. Efficient resources will be created to reach the point of maximum satisfaction, as fairly as possible without wrongdoing other individuals. In IT here are various values ​​and norms that must be considered in terms of allocating and distributing income. These values ​​and norms make it different from conventional. Islam does recognize the existence of individual ownership in which individuals are free to use it, but it must be emphasized that in relation to the freedom of ownership, in which property belongs to the individual it is not an absolute possession, because in the Qur'an itself explains that every property that belongs to the individual we have other people's rights including the rights of the poor. SEvery economy is said to have achieved optimal efficiency if it has utilized all the potential of limited human and material resources in such a way that the maximum quantity of goods and services can satisfy needs with a good level of economic stability and a sustainable growth rate in the future. In order for the distribution allocation to provide significant efficiency, it is necessary to pay attention to the principles; 1) justice and equity; 2) the principles of brotherhood and compassion; 3) the principle of social solidarity. The Islamic economic system consists of zakat as a model for individual compulsory distribution, waqf as an instrument of individual distribution for society, inheritance as an instrument of distribution in the family, infaq and alms as an instrument of distribution in society. The distribution policy taught by Islam is closely related to wealth so that it does not accumulate in certain groups in society and encourages the creation of distribution justice. In this context, the government is required not to side with one particular group or class so that the distribution process can run fairly.   Distribusi pendapatan merupakan aspek terpenting karena berkaitan dengan bagaimana individu dapat mengalokasikan sumber daya secara efisien. Sumber daya yang efisien akan tercipta dapat mencapai titik kepuasan maksimal, dengan seadil-adilnya tanpa menzalimi individu yang lainnya. Dalam Islam terdapat berbagai nilai dan norma-norma yang harus diperhatikan dalam hal pengalokasian maupun pendistribusian pendapatan. Nilai dan norma-norma inilah yang menjadikan berbeda dengan konvensonal. Islam memang mengenal adanya kepemilikan individu yang mana dengan kepemilikan tersebut individu bebas memanfaatkannya, namun harus digaris bawahi terkait kebebasan kepemilikan, dimana dalam kekayaan yang menjadi milik individu bukan merupakan suatu kepemilikan yang mutlak, karena dalam Al-Qur’an sendiri menjelaskan bahwa setiap harta yang kita miliki terdapat hak-hak orang lain termasuk hak orang miskin. Setiap perekonomian dikatakan telah mencapai efisiensi yang optimal apabila telah mengguakan seluruh potensi sumber daya manusia dan materi terbatas sedemikian rupa sehingga kuantitas barang dan jasa maksimum dapat memuaskan kebutuhan dengan tingkat stabilitas ekonomi yang baik dan tingkat pertumbuhan berkesinambungan pada masa yang akan datang. Agar alokasi pendistribusian memberikan efesiensi yang signifikan maka perlu diperhatikan prinsip-prinsip; 1) keadilan dan pemerataan; 2) prinsip persaudaraan dan kasih sayang; 3) prinsip solidaritas sosial. Sistem ekonomi Islam terdiri dari zakat sebagai model distribusi wajib individu, wakaf sebagai instrumen distribusi individu untuk masyarakat, waris sebagai instrumen distribusi dalam keluarga, infak dan sedekah sebagai instrumen distribusi di masyarakat. Kebijakan distribusi yang diajarkan Islam sangat berkaitan dengan harta agar tidak menumpuk pada golongan tertentu di masyarakat serta mendorong terciptanya keadilan distribusi. Dalam konteks ini, pemerintah dituntut untuk tidak berpihak pada satu kelompok atau golongan tertentu agar proses distribusi dapat berjalan dengan adil.